Value of Time, Choice of Mode, and the Subsidy Issue in Urban Transportation - Moses, Leon N.; Williamson,, Harold F. (Journal of Political Economy, 1963)
The last two decades have clearly shown that increased automobile ownership and highway construction can facilitate profound redistributions of population and economic activity within metropolitan areas. These changes are related in a fundamental way to many of the social and economic difficulties of our large, mature, central cities: loss of middle and upper income groups to the suburbs, declining retail sales in downtown areas, erosion of the tax base, shift of manufacturing and service establishments to suburban areas, decline of mass transit service and patronage, and increased traffic congestion. There is a great deal of support for the view that there has been too much highway construction and that the time has come to help public transportation. This paper explores some of the issues involved in a program of assistance to public transportation.